Constructed Wetland Units Filled with Waterworks Sludge for Remediating of Wastewater Contaminated with Congo Red Dye - Ayad A. H. Faisal; Basim J. Bedah, Basim J. Bedah; Al-Hashimi, Osamah (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The disposal of textile effluents to the surface water bodies represents the critical issue especially these effluents can have negative impacts on such bodies due to the presence of dyes in their composition. Biological remediation methods like constructed wetlands are more cost-effective and environmental friendly technique in comparison with traditional methods. The ability of vertical subsurface flow constructed wetlands units for treating of simulated wastewater polluted with Congo red dye has been studied in this work. The units were packed with waterworks sludge bed that either be unplanted or planted with Phragmites australis and Typha domingensis. The efficacy of present units was evaluated by monitoring of DO, Temperature, COD and dye concentration in the effluents under the variation of detention time (1-5 day) and dye concentration (10-40 mg/L). The maximum removal of dye and COD were 98 and 82% respectively for 10 mg/L of Congo red dye after five-day hydraulic retention time (HRT). The results have shown that the removal of COD and dye concentration significantly increased with higher contact time and lower dye concentration. The values of monitored parameters adopted to evaluate the wastewater quality (i.e. DO, COD and Congo red dye) are satisfied the requirements of irrigation water. The dye concentration variation in the effluent with contact time was formulated efficiently by Grau kinetic model. Functional groups (specified by FT-IR analysis) have a remarkable role in the entrapment of dye on the waterworks sludge bed.